Estimation of local linear heat rate jump values in the variable loading mode - S. N. Pelykh; R. L. Gontar; T. V. Tsiselskaya (Ядерна фізика та енергетика)
A method of the WWER-1000 fuel element cladding durability analysis using the energy creep theory makes it possible to determinate the WWER-1000 reactor permissible operation time for the mode of varying loading. But the WWER-1000 axial segments and fuel assemblies differ greatly in their local linear heat rate jump value. It has been found that the value of linear heat rate is one of key parameters that influences on a fuel element cladding durability in the mode of variable loading. So, determination of the WWER-1000 reactor permissible operation time for the mode of varying loading requires estimation of the WWER-1000 local linear heat rate jumps.